2002
DOI: 10.1152/ajpendo.00570.2001
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I and insulin regulate eIF4F formation by different mechanisms in muscle and liver in the ovine fetus

Abstract: The mechanisms by which insulin-like growth factor I (IGF-I) and insulin regulate eukaryotic initiation factor (eIF)4F formation were examined in the ovine fetus. Insulin infusion increased phosphorylation of eIF4E-binding protein (4E-BP1) in muscle and liver. IGF-I infusion did not alter 4E-BP1 phosphorylation in liver. In muscle, IGF-I increased 4E-BP1 phosphorylation by 27%; the percentage in the gamma-form in the IGF-I group was significantly lower than that in the insulin group. In liver, only IGF-I incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
28
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 62 publications
(78 reference statements)
8
28
2
Order By: Relevance
“…The percentage of highly phosphorylated 4E-BP1 was 28% (Fig. 1), whereas this figure was 40% in a similar fed study (13), suggesting that decreased fetal protein synthesis associated with maternal fasting is in part due to a decrease in the efficiency of translation initiation.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…The percentage of highly phosphorylated 4E-BP1 was 28% (Fig. 1), whereas this figure was 40% in a similar fed study (13), suggesting that decreased fetal protein synthesis associated with maternal fasting is in part due to a decrease in the efficiency of translation initiation.…”
Section: Discussionmentioning
confidence: 86%
“…Highly phosphorylated p70S6K migrates more slowly than less phosphorylated protein (13). Using a p70S6K pan-antibody, we found that both insulin and IGF-I slowed down p70S6K migration rate on SDS-PAGE, suggesting that the two peptides increase p70S6K phosphorylation (Fig.…”
Section: Fasting Alters Eifs In the Fetusmentioning
confidence: 78%
See 3 more Smart Citations